Risk Management of Tarutama Nusantara - Mahdzum Zahid (Journal of Islamic Economics Perspectives, 2022)
A country's economy can grow and develop because it is followed by developments in the real sector. In today's era of globalization, competitive conditions in the market are rarely predictable. The inability to predict it can pose a lot of risks coming. So management is needed. The risk management function is the responsibility of all levels of management and work units in each business function, with the task of identifying risks and managing risks according to the authority attached to each. This paper examines the risk management in KOPA TTN using a qualitative approach. The results show that there are several steps taken to anticipate the occurrence of existing risk management.